Effect of wastewater disposal on the bacterial and archaeal community of sea sediment in an industrial area in China. Issue 2 (6th May 2014) - Zhang, Yan; Chen, Lujun; Sun, Renhua; Dai, Tianjiao; Tian, Jinping; Liu, Rui; Wen, Donghui
Abstract: Human activities usually leave footprints in the environment. By using 454 pyrosequencing, the impact of effluent from an industrial park on the coastal microecology in Hangzhou Bay, China, was interpreted by analysing the microbial communities of the activated sludge from three wastewater treatment plants and the sediment from the effluent receiving area. Based on richness and biodiversity, the sediments were more diversified than the activated sludge, although the seawater environment was highly contaminated. Both bacterial and archaeal communities were niche-determined. The bacterial phylum Proteobacteria dominated in all samples; and certain pollutant-resistant genera, such as Thauera and Truepera, were found in all samples. Archaeal phyla Euryarchaeota and Thaumarchaeota dominated the activated sludge and sediment samples, respectively. According to the analysis of shared operational taxonomic units (OTUs) and reads among different samples, more bacterial OTUs and reads were shared between two samples from sites with a direct effluent connection, showing a clear correlation between the wastewater treatment plants and the effluent receiving bay area. The impact of second-hand pollution can be evaluated by comparing the bacterial community in different eco-environments with a direct effluent connection, especially when pristine samples are not available. Abstract : Based on the similarity of bacterial communities, not archaeal ones, a correlation was found from WWTPs to effluent receiving bay, implying the ecological change under the impact of human activity.